PREFERENSI MAHASISWA DALAM AKSES INFORMASI DARI INTERNET DIBANDINGKAN BUKU - Alifya, Sabrina; Calista Mayla Azalia; Adika Lestari; Muhammad Rafin Nadzif; Aldeagustin Dwi Mulviani; Joko Tri Nugraha (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
A diverse array of information sources in multiple formats offers students avenues to satisfy their academic requirements. The objective of this study is to elucidate students' preferences in information retrieval, specifically contrasting the utilization of the internet and traditional books as primary references. The rapid advancement of technology has significantly shaped the methodologies by which students pursue information for both scholarly and non-scholarly objectives. This research adopts a quantitative framework via an online survey encompassing 82 students from a range of academic disciplines at Tidar University. The findings indicate that a predominant portion of respondents favors the internet due to its ease of access and the extensive range of information it provides. Conversely, a segment of students continues to depend on books, attributing to them a greater sense of credibility and a more comprehensive presentation of information. This observation signifies a noteworthy transition in information-seeking preferences, even as books retain their relevance within specific contexts. Consequently, this study advocates for initiatives aimed at enhancing students' competencies in selecting and critically appraising information, particularly from digital mediums.